FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI KELUARGA DALAM MENCEGAH KEKAMBUHAN PADA KLIEN GANGGUAN JIWA - Pramana Pramana; Veny Elita; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Relapse of a mental disorder is a reappearance of symptoms of a real mental disorder. One of the triggers for relapsein patients with mental disorders is family motivation. This study aims to determine the factors associated with familymotivation in preventing recurrence in the client mental disorders.The design of this study was a cross sectional studywith a sample of 81 people taken using purposive sampling technique, univariate data analysis and bivariate with chisquaretest. The result of the research showed that most of respondent's characteristic were age group of elderly (46-55years old), male majority and highest education was high school. There is a relationship between knowledge (p value0,000, OR = 138), economic level (p value 0.049, OR = 2.96), access to health services (p value 0.013, OR = 3.49),confidence (p value 0.001, OR = 5,58), environment (p value 0,000, OR = 13,19) with family motivation in preventingrelapse on client mental disorder. It is expected that families should take routine monthly recharge patients accordingto the advice of health workers, to prevent patients from recurrence and re-hospitalization and to socialize again in thesocial environment.Keywords : Mental disorders, motivation family, prevention of relapse